Clinical characteristics, triggering etiologies, and response of plasmapheresis in thrombotic microangiopathy in Taiwan. Issue 20 (21st May 2021) - Chung, Ching-Hu; Tsai, I-Jung; Tseng, Min-Hua; Chou, Hsin-Hsu; Tain, You-Lin; Tsai, Jeng-Daw; Chiou, Yuan-Yow; Chiou, Yee-Hsuan; Lin, Ching-Yuang
Abstract : Abstract: Thrombotic microangiopathy (TMA) syndromes are extraordinarily diverse in clinical presentations and etiologies. However, there are still a limited number of large cohort studies focusing on the underlying causes, outcomes, and response to plasmapheresis. A retrospective study was designed to understand trigger etiologies, organ dysfunctions, clinical outcomes, and efficacy of plasmapheresis in patients with TMA. The whole population of Taiwan was set up into 2 cohorts: 875 patients with TMA in the 2006 cohort (2006–2010) and 1352 patients with TMA in the 2011 cohort (2011–2015). One hundred ninety-five patients in the 2006 cohort and 272 patients in the 2011 cohort were under plasmapheresis treatment. The common underlying etiologies were pregnancy, followed by systemic lupus erythematosus, rheumatoid arthritis, transplantation and drugs, which were significantly higher than the control group. Stroke, seizure, arterial thrombosis, vascular stenosis, hypertension, myocardial infarction, and pancreatitis were the main clinical signs and extra-renal involvements. In the multivariate regression analysis, stroke, arterial thrombosis, peripheral arterial disease, and uremia were significantly higher compared with the control group. The mortality rate in TMA under plasmapheresis was significantly higher than all TMA cases (39.33% vs 15.39% in the 2006 cohort and 39.27% vs 15.06% in the 2011 cohort). This study indicated the spectrum of underlying causes, extra-renal characteristics, and the response to plasmapheresis of patients with TMA in Taiwan. Of note, the poor clinical outcomes of plasmapheresis in patients with TMA might highlight the masked underlying etiology or worse disease condition that should be noticed. Abstract : Supplemental Digital Content is available in the text